Quantitative Analysis in Traditional Knowledge of Wild Medicinal Plants Used to Treat Livestock Diseases by The Paliyar’s Tribe of Sadhuragiri Hillstamil Nadu, India - Kamatchi, Aadhan; Parvathi, Anand Subramaniam (Asian Journal of Pharmaceutical Research and Development, 2020)
An ethno-medicinal study of ethno-veterinary medicines among the local indigenous peoples of the villages of Sadhuragiri Hills, Southern Western Ghats, Virudhunagar district of Tamil Nadu, India were carried out during the period of July 2016 and March – 2018. About 90% interviewed people gained their knowledge of traditional medicine from their parents and grandparents and others gained from neighbors and co-producers. It has been observed that older persons and traditional healers have greater knowledge about traditional medicines than younger persons. Ethno-veterinary uses of 120 species belonging to 59 families have been documented in this study for their interesting therapeutic properties of various veterinary ailments such as Wound healing, Fever, Diarrhoea, Cold, Skin diseases, Bone fracture, Foot and mouth, Poison bite, Eye diseases, Low milk yielding, Fly repellent, Stomach pain, Anti-inflammatory, Cough, Swelling, Throat pain, Ear pain, Anorexia etc. Leaves thirty one species (37.2%) followed by Seed, Bark, Fruit, Latex and latex were most frequently used plant parts for ethno veterinary medicine. Usually fresh materials were used for medicinal preparation. The most frequently used routes of drug administration have been oral followed by dermal. Our study recommend that, documenting the medicinal plants and associated indigenous knowledge can be used for conservation and sustainable use of medicinal plants in the area and for validation of these plant preparations for ethno-veterinary treatment.